The Effect of Capital Structure, Profitability Ratio and Liquidity Ratio on Share Prices - Firman Ardiansyah; Agus Sukoco; Ani Wulandari (NAROTAMA UNIVERSITY, Indonesia, 2020)
This study aims to analyze the effect of the influence of capital structure, profitability ratio and liquidity ratio on share prices (studies on manufacturing companies in southeast asia) 2017-2019. The sample used was 15 manufacturing companies with purposive sampling method. This research used quantitatif approach. The data collection techniques used are documentation in the form of secondary data and library research. The analysis of this research uses multiple linear regression. The results of this study are the capital structure, liquidity ratio and rentability ratio have a significant positive effect on stock prices simultaneously and partially.